Impacts of protein supplementation during mid gestation of beef cows on maternal physiology, and skeletal muscle metabolism - Moreno Meneses, Javier Andrés (2021)
There are still gaps in the knowledge that need to be filled about how the dams adapt physiologically to avoid losses during pregnancy and how these adaptations can compromise their reproductive efficiency. There are currently about 56 million beef cows in Brazil that can benefit from advances in knowledge in this area of knowledge. Therefore, this research aimed to determine the effect of protein supplementation (SP) during mid-gestation in cows fed low-quality forage on performance, food intake, physiology, and protein metabolism in maternal skeletal muscle tissue. Fifty-two multiparous cows with 490 kg ± 17.8 body weight (BW), 5.63 ± 0.52 body condition score (ECC), Tabapuã breed, and male and female calf carriers were randomly distributed in one of the two treatments: Supplementation with 40% crude protein (CP) or 3.5g / kg BW (SUP; n = 26) or not supplemented 0% CP (CON; n = 26). Between 100 to 200 days of gestation, the cows were housed in individual pens and subjected to different levels of feeding: the CON being conformed to a basal diet (corn silage + sugarcane bagasse, reaching 5.5% CP plus mineral mixture) and the SUP conformed by the basal diet + protein supplementation. CP and ECC were determined every 30 days until pre-delivery. Feed intake was monitored individually until pre-delivery, blood samples, skeletal muscle tissue biopsies, and pulsatility index (PI) and resistance (IR) were collected at 200 and 270 days of gestation. The results will be published in two articles. In the first article, SP increased the body reserves represented in higher maternal CP, gestational tissues, rib eye area, and croup (P ≤ 0.01). CON cows lost almost one point of ECC, while SUP gained 0.59 points of ECC for 100 days. However, in the peripartum SUP cows mobilized a greater amount of maternal tissue (P ≤ 0.01). Supplementation increased forage intake, total dry matter, and apparent total digestibility of nutrients, and efficiency of microbial synthesis (P ≤ 0.01). CON cows had higher RI and PI (P ≤ 0.01) in mid-gestation. In the second article, SUP cows had increased plasma concentrations of glucose, insulin, and IGF-1, however, non-esterified fatty acids were higher (P ≤ 0.01) in CON. SUP cows showed approximately 50% increases in the total circulating amino acid concentration (P = 0.03), and between 30 and 40% increases in mRNA expression of markers related to protein synthesis and degradation during pregnancy. The results suggest that SP at 3.5 g / kg of BW in the mid-gestation can be useful to improve the energy status of cows, in addition to allowing a greater flow of nutrients to the uterus, allowing for adequate fetal growth and development, which will help preserve maternal tissue reserves when maintained on low quality pasture.